Comparison of ionic liquid, acid and alkali pretreatments for sugarcane bagasse enzymatic saccharification - Yoon, Li Wan; Ngoh, Gek Cheng; Chua, Adeline Seak May; Hashim, Mohd Ali (Wiley, 2011)
Background: Much attention has been given to applying ionic liquids (ILs) as an alternative pretreatment method for lignocellulosic biomass. This study aims to select the most suitable type of IL for pretreating sugarcane bagasse (SCB). The potential of ILs for pretreatment was evaluated and compared with conventional pretreatment media, acids and alkalis. The performance of the pretreatment media was evaluated based on the amount of reducing sugar produced from enzymatic saccharification, the energy requirement, and changes in the chemical structure and crystallinity index of the pretreated bagasse. Results: 1-ethyl-3-methylimidazolium acetate [EMIM]oAc was selected as the most suitable IL for SCB pretreatment. The optimum yields of reducing sugar obtained from [EMIM]oAc-, alkali-, and acid-pretreated SCB were 69.5%, 92.8% and 41.3%, respectively. Although a lower yield of reducing sugar was obtained, [EMIM]oAc pretreatment required the least energy to pretreat 1 kg of SCB. Moreover, the percentage of SCB loss during [EMIM]oAc pretreatment was the lowest. [EMIM]oAc-pretreated SCB also had the lowest crystallinity index (CI) with the most amorphous structure. Conclusion: [EMIM]oAc appears to be another option for pretreating SCB, and other issues such as the recyclability of [EMIM]oAc is worth investigating. © 2011 Society of Chemical Industry.